Classical music and postmodern knowledge - Kramer, Lawrence, 1946- (Berkeley : University of California Press, 1995)
A leading cultural theorist and musicologist opens up new possibilities for understanding mainstream Western art music--the ""classical"" music composed between the eighteenth and early twentieth centuries that is, for many, losing both its prestige and its appeal. When this music is regarded esoterically, removed from real-world interests, it increasingly sounds more evasive than transcendent. Now Lawrence Kramer shows how classical music can take on new mean.
Intro -- Contents -- Musical Examples and Figures -- Preface -- Acknowledgments -- One. Prospects -- Two. From the Other to the Abject -- Three. Music and Representation -- Four. Musical Narratology -- Five. Felix Culpa -- Six. The Lied as Cultural Practice -- Seven. Cultural Politics and Musical Form -- Eight. Consuming the Exotic -- Epilogue à 4 -- Appendix. Mendelssohn -- Notes -- Index
Includes bibliographical references (pages 255-289) and index.
Print version record.
In English.
JSTOR
Keywords: Music -- Philosophy and aesthetics; Postmodernism; Musique -- Philosophie et esthétique.; Postmodernisme; MUSIC -- Genres & Styles -- General; MUSIC / Genres & Styles / Classical; Music -- Philosophy and aesthetics; Postmodernism; art history; case study; charles ives; classical music; cultural politics; cultural trope; daphnis and chloe; desire; gender; goethe; haydn; literary theory; mendelssohn; music history; music; musical expression; musical form; musical heritage; musical narratology; musicology; performative; postmodern music; postmodernism; postmodernity; representation; tutelage; western art music; western music